Condições que favorecem ou desfavorecem a aprendizagem relacional em crianças com histórico de fracasso escolar - Arantes, Ana Karina Leme (2008)
The stimulus equivalence concept has been used by behavior analysts as an instrument to systematic verifications of new and complex repertories, offering an operational specification of symbolic behavior and distinguishing between two kinds of relational stimulus pairs: conditional relations and equivalence relations. The most often used procedure to verify emergence of equivalence relations is the matching to sample (MTS), in which two conditional relations between stimulus pairs are taught. In this procedure the experimenter does not know the baseline stimulus control topographies and the subject answers, although could be similar to those expected, may include different control topographies, being some controlled by selection and others controlled by rejection. One alternative possibility to verify different baseline control relations is the use of special procedures to induce and identify these relations, like the blank comparison procedure. In this procedure, a black square is introduced on the baseline conditional discrimination trials to block the stimulus for the subject. The present study used the blank comparison procedure with seven normally developing children with school failure history, to separated verify the selection and rejection topographies and the differences in the emergence of equivalence relations. Different arbitrary visual stimulus sets were used in each training: conditional discriminations with both selection and rejection topographies, conditional discriminations only with rejection topographies in the BC relations, and conditional discriminations only with selection topographies in the BC relations. The blank comparison procedure was used to generate these controls on the baseline conditional discriminations. All participants met high percents of correct answers after the training with both control topographies and demonstrating equivalence, although some children needed other procedures to remediate fails in the training. After the trainings with only rejection or selection control in the BC relations, no children obtain a positive equivalence test outcome, pointing that guarantee of both rejection and selection control topographies could minor the emergent relations test outcomes variability in the matching to sample procedures.